ANALISIS PERBAIKAN TANAH DASAR MENGGUNAKAN METODE GEOTEKSTIL - Saiful Anam; Laily Endah Fatmawati; Herry Widhiarto (LPPM Universitas Abdurrab, 2023)
Soil acts as a building material in various types of civil engineering work, on the other hand land plays a role as a support for building foundations such as embankments, highways and railroads. Soil improvement is a type of soil stability that is useful as soil improvement and performance required by technical requirements. In an effort to increase the carrying capacity of the soil, several methods can be used, such as: soil improvement using Replecement Soil, PVD Method, Preloading, Micropile, Geotextiles, etc. In this study, the geotextile method was used as an alternative reinforcement to find a larger and better safety number (SF) for soil conditions adjacent to (Groundwater Table), and can be the most effective alternative soil improvement method. Based on the analysis of the data, it was concluded that the total load (q) is 31 layers of non-woven which is 2 layers, with a length of geotextile (L) of 1.825 m. The safety factor geotextile method non-woven = 2.4.